2006
DOI: 10.1038/sj.ijo.0803178
|View full text |Cite
|
Sign up to set email alerts
|

Change in height, weight and body mass index: Longitudinal data from the HUNT Study in Norway

Abstract: Objective: The aim of this study was to analyse changes in body weight and height, and the changes in the prevalence of overweight and obesity. Design: Prospective population based study with 11-year follow-up. Subjects: Norwegian men (n ¼ 21565) and women (n ¼ 24337) aged 20 years or more who participated in two health surveys, the first in 1984-1986 and the other in 1995-1997. Measurements: Height and weight were measured by using standardised procedures at both surveys, and we computed body mass index (BMI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
111
3
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(145 citation statements)
references
References 16 publications
(18 reference statements)
25
111
3
6
Order By: Relevance
“…This study demonstrates a large increase in the prevalence of overweight and obesity in this Glasgow population between 1991 and 2000, consistent with recent data from other European countries (Berg et al, 2005;Drøyvold et al, 2006), Changes in weight and WC in a Scottish population M Ebrahimi-Mameghani et al the United States (Fine et al, 1999) and Australia (Ball et al, 2003). While significantly fewer women than men maintained a stable weight over the 9-year period, we found no significant difference between the genders, in either age cohort, in the mean 9-year weight change or mean BMI.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study demonstrates a large increase in the prevalence of overweight and obesity in this Glasgow population between 1991 and 2000, consistent with recent data from other European countries (Berg et al, 2005;Drøyvold et al, 2006), Changes in weight and WC in a Scottish population M Ebrahimi-Mameghani et al the United States (Fine et al, 1999) and Australia (Ball et al, 2003). While significantly fewer women than men maintained a stable weight over the 9-year period, we found no significant difference between the genders, in either age cohort, in the mean 9-year weight change or mean BMI.…”
Section: Discussionsupporting
confidence: 91%
“…We Changes in weight and WC in a Scottish population M Ebrahimi-Mameghani et al did not investigate the role of behavioural factors known to impact on weight (for example, dietary intake, physical activity and smoking status) in this analysis, which would have provided further information to inform the development of effective strategies to prevent weight gain and promote weight maintenance. Nevertheless, the age-related weight gain patterns reported in this study are consistent with those reported in other populations (Ball et al, 2003;Drøyvold et al, 2006). The general similarities in weight gain across occupational groups seen in this study suggest that insidious weight gain is a widespread problem that crosses all social boundaries.…”
Section: Discussionsupporting
confidence: 89%
“…For women, BMI is lower compared to data from the HUNT study (35) and the Tromsø study (36). For men, the BMI results are in line with the HUNT data in both age-groups and slightly higher compared to the Tromsø data for the 53-55-year-olds.…”
Section: Cardiovascular Disease Risk Factorssupporting
confidence: 72%
“…Some authors point to a decrease in SMM and Ap SMM as age increases 11 , and this is an important factor associated with sarcopenic obesity. In our study, age was not significantly different between sarcopenic and non-sarcopenic groups and did not correlated with residual Ap SMM.…”
Section: Discussionmentioning
confidence: 99%
“…Sedentary lifestyle is an important risk factor related to weight gain and the decrease in SMM 10 . Obese people tend to be less physically active when compared with normal weight people, which could contribute to decreased mugenescle strength 11 . Thus, general muscle loss can lead to a reduction in Resting Metabolic Rate and the reduction of energy expenditure during exercise and daily physical activities, which may further aggravate the sedentary state, and the accumulation of fat mass 2,12 .…”
Section: Introductionmentioning
confidence: 99%